Answer:
Expression in
term is
![T_n =2(6-n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/suq74frdsc15iui9j5obbkd6lfpq7ehm0b.png)
Explanation:
Arithmetic sequence 10,8,6,4,.....
first term a = 10
second term = 8
number of terms = n
common difference d = Second term - First term =
![8-10 \ =\ -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u5j1766t3v4m6h4flxk98wfi4yw8xejve9.png)
Now by using Arithmetic Progression Formula which states
![T_n = a+(n-1)d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/to89p962efh7bz0nb7u6cs4s7oxr3ept8a.png)
Substituting given values in the above expression we get
![T_n= 10+((n-1)*-2})= 10-2n+2= 12-2n= 2(6-n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ouchiabww9wj6afvki6ou45zzq8yvmjgrf.png)